THE REACTION OF CHARISMATIC AND TRANSFORMATIONAL LEADERSHIP TOWARDS MACHIAVELLIANISM IN ORGANIZATIONS - Lorensia Lorensia; Andi Ina Yustina; Mila Austria Reyes (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
Machiavellianism is one of the dark triads behavior portrayed as a negative characteristic that could engage with unethical behavior and reduce the social relationship between staff and upper staff. Another study has found that leadership style could minimize high Machiavellianism in a company, and each leadership style's reactions have been warranted to be studied. Transformational and charismatic leadership are excellent leadership that could reduce high Machiavellianism. The data was gathered by spreading questionnaires to the company's employees; 189 respondents' data have been analyzed using SEM-PLS. This study shows that charismatic and transformational leadership have a negative and significant relation to Machiavellianism. This study suggests testing some mediators in order to stronger the relationship between those variables.